Fostering a Digitally Inclusive Aging Society in China : The Potential of Public Libraries - World Bank (Washington, DC, 2014)
The World Bank has been supporting this policythrough theprogram China Rural Information and Communications: Technical Assistance on Design and Impact Evaluation, which aims to support the government make decisions about potential scaling up of innovative ICT pilot projects and to generate and disseminate knowledge about the impacts of ICT in rural China. Three activities were undertakenwith a focus on a trio of provinces (Guizhou, Jilin, and Shandong): (a) a demand survey to assess rural ICT access and attitudes; (b) a library study including scoping the status of ICT use in rural libraries; and (c) a limited impact evaluation to examine how ICT interventions have affected rural users.